A magyar etnikai térszerkezet változásai a honfoglalástól napjainkig - Kocsis, Károly (Tér és Társadalom, 1996)
The author acquaints us with the transitions of the Hungarian ethnic territory during the past 1100 years, divided into seven chapters according to the main milestones in Hungarian history (1526, 1711, 1849, 1920, 1938, 1945). The study telis us that there are hardly any nations in Europe the population and ethnic territory of which changed during the past centuries as strikingly as those of the Hungarians. Perhaps it is only the Croatians – fragmented in the conflict zone of the front line between the Christians and Muslims in the 15th-17th centuries – and the Polish suffering in the German-Russian conflict zone who had a situation similar to the Hungarian one, if we look at the development of their ethnic territory and its frequent expansions and contractions. The rhapsodic changes of the ethnic spatial structure of Hungary were after all connected to the geographical location of the Carpathian Basin, that, in the meeting point of Western and Eastern Christianity and the Islamic world (15th-19th centuries) and that of the German and Slavic ethnic blocks, had a basic influence on historical events. Also, with its natural geographical endowments, in connection with the lifestyle of the Hungarian nation, it determined the size of the ethnic territory of the Hungarians and the limits of growth in the Medieval Ages.